Left behind [compact disc, unabridged] : a novel of the Earth's last days - LaHaye, Tim, 1926-2016 (LaHaye, Tim, 1926-2016. Left behind series, 1998)
Pilot Rayford Steele begins to suspect that something is horribly wrong when most of the passengers on his plane disappear without a trace. After landing he finds that millions of people around the world have also vanished, leaving behind disorderliness and confusion. Soon he and reporter Buck Williams, a passenger on Rayford's flight, seek out the truth behind the mass disappearances, which leads to some very sinister forces.